(untitled) (World Bulletin of Management and Law, 2023)
For the inaugural episode of a podcast featuring discussions with international legal scholars, I had the privilege of hosting my esteemed instructor, Dr. Nasiruddeen Muhammad, hailing from the University of Dubai, UAE. During my time as a student at the University of Dubai, Dr. Nasiruddeen delivered lectures on subjects such as ADR, International Commercial Arbitration, International Negotiations, and the Economic Procedural Law of the UAE, all of which he skillfully linked to global legal practices. Back then, I was truly impressed by the depth of his legal knowledge, the expansiveness of his intellectual horizons, his unwavering attentiveness, and his warm kindness. Fast forward to 2018, when I returned to Uzbekistan, and our mentorstudent relationship with Dr. Nasiruddeen endured. Recently, he graced Tashkent with his presence during the Uzbek-Arbitration Week 2023, held at Tashkent State University of Law, where he actively participated. During his visit, he also spent several days as an honored guest in our country.